Pengoptimalan Rute untuk Minimasi Biaya Distribusi pada CV.DNY - Kurnia, Mirza Aji; Handayani, Wiwik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The distribution route problem at CV.DNY is related to the lack of optimal route determination because delivery routes are determined only based on the order of goods received first. Determining the route in the distribution process is an important factor for the company because it affects the company's distribution costs. CV. DNY is a logistics company that operates in the sector of delivering goods to consumers. Based on field studies conducted, the company has not been able to determine the optimal route. The aim of this study is to increase the efficiency of the routes used so that shipping costs can be saved. The method used in this research is a minimum spanning tree. The results of the research show that the minimum spanning tree method obtains a shorter route with a distance of 4557 km compared to the company's initial route of 5318 km, experiencing distance savings of 761 km and minimizing distribution costs of IDR 5,174,800. So it can be concluded that the minimum spanning tree method uses POM-software The company's QM (Program Operations Management – ​​Quantitive Method) achieves delivery route savings and cost minimization.